El Programa de Creadores de Mercado peruano como estrategia de desarrollo del mercado de deuda pública - Rodríguez A., Augusto (2006)
In recent years, public debt management strategies have been applied in emerging markets so as to reduce debt exposure to financial risks and thereby to adverse external shocks. In Peru, towards the end of March 2003, a Market Makers Program was set up, with the main objective of developing a public debt market denominated in nuevos soles, and thereby to encourage a domestic capital market. Important results have been achieved in the first four years: amongst other things, the formation of a nuevos soles yield curve with a maturity of 20 years, an increase in the domestic sovereign bonds liquidity, and a reduction in the public debt currency mismatch. This paper analyzes the impact of the program. The evidence suggeststhat if policy makers fail to consider issues that will help build on these successful results, then market development may well be limited in the years to come.